Cardiovascular Risk Factors and Its Management - Islam, QT; Ekram, ARM Saifuddin; Ali, ASM Shawkat; Ali, M Ayub (TAJ: Journal of Teachers Association, 2009)
Major risk factors for cardiovascular diseases are hypertension, diabetes mellitus, dyslipidaemia, smoking and obesity. In this review article, we have tried to discuss the updated management of each major risk factor. doi: 10.3329/taj.v20i1.3096 TAJ 2007; 20(1): 71-78